Percutaneous Vacuum-Assisted Thrombectomy Device Used for Removal of Large Vegetations on Infected Pacemaker and Defibrillator Leads as an Adjunct to Lead Extraction - Schaerf, Raymond H M (J Atr Fibrillation, 2016)
This case series reports our early experience with a minimally invasive percutaneous method of safely removing large vegetations during lead extraction in septic cardiac implantable electronic devices (CIED). Debate exists concerning the management of vegetations involving these devices. Lead extraction is mandated for infections, but vegetations may embolize, causing complications. Surgical debridement is recommended; alternatives include cardiopulmonary bypass, minimally invasive thoracotomy, or transatrial approaches. The AngioVac device allows percutaneous right heart bypass and suction removal of vegetations under echocardiographic and fluoroscopic guidance. This case series describes our first 20 patients, all critically ill with persistent sepsis and vegetations despite long-term antibiotics. This series includes patients who would not have been eligible for alternative procedures due to contraindications and highlights the potential role of this new technology.